Higher Family Affluence is Associated With Multi-Sport Participation Among Irish Youth - Kearney Philip E; Sherwin Ian; O'Brien Wesley; Nevill Alan M; Ng Kwok (SAGE PUBLICATIONS INC, 2025)
The impact of early single sport participation among young people has received much attention, with both sport leaders and pediatricians advocating multi-sport participation at least until early adolescence. In this study we explored the association between family socioeconomic status and level of Irish youth specialization in sport. We relied on data from the Children's Sport Participation and Physical Activity (CSPPA) study, involving a representative sample of 3499 Irish children and adolescents aged 10-15 years. We analyzed data from questions related to the number of sports played, the number of days per week the youth were engaged in sport, and family affluence (as a proxy measure for socioeconomic status). Youth sport specialization before 12 years of age (males 5.7%; females 4.2%) and even between 13-15 years of age (males, 7.8%; females, 5.8%) was uncommon. However, lower levels of specialization were associated with higher socioeconomic status in that more children with high family affluence participated in multiple sports. Careful consideration should be given to whether low socioeconomic status may act as a barrier to participation in multiple sports.